"He has a way gayer Facebook than I do": Investigating sexual identity disclosure and context collapse on a social networking site. (June 2016) - Duguay, Stefanie
This study extends previous research into social networking sites (SNSs) as environments that often reduce spatial, temporal, and social boundaries, which can result in collapsed contexts for social situations. Context collapse was investigated through interviews and Facebook walkthroughs with 27 LGBTQ young people in the United Kingdom. Since diverse sexualities are often stigmatized, participants' sexual identity disclosure decisions were shaped by both the social conditions of their online networks and the technological architecture of SNSs. Context collapse was experienced as an event through which individuals intentionally redefined their sexual identity across audiences or managed unintentional disclosure. To prevent unintentional context collapse, participants frequently reinstated contexts through tailored performances and audience separation. These findings provide insight into stigmatized identity performances in networked publics while situating context collapse within a broader understanding of impression management, which paves the way for future research exploring the identity implications of everyday SNS use.